OPTIMAL TUNING OF MECHANICAL SYSTEMS BY APPLICATION OF A PNEUMATIC TUNER OF TORSIONAL OSCILLATION - Jaroslav HOMIŠIN (Scientific Journal of Silesian University of Technology. Series Transport)
Reducing the dynamic load of any mechanical system can be achieved when the torsional vibration magnitude is optimized by applying a pneumatic tuner of torsional oscillation. Changing the torsional stiffness of a pneumatic tuner can be accomplished by changing the pressure of the gaseous medium, out of operation or during the operation of a mechanical system. This results in two suggested methods of tuning: (i) tuning of torsional oscillating mechanical systems that are out of operation, which fulfils the conditions for mechanical system tuning; (2) tuning mechanical systems during an operation in a steady state, thus ensuring the conditions of so-called continuous tuning of the given systems. The aim of this paper is to present the possibility of controlling torsional oscillation of a mechanical system that is out of operation by applying a tangential pneumatic tuner of torsional oscillation.